Analysis of the coffee market in Colombia: production and consumption - Santafé Sánchez, Divine Lorrain (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
The purpose of this research is to detect patterns in coffee production. Coffee plant figures were examined at both global and national levels, using data provided by the National Federation of Coffee Growers (FNC). Various factors such as climate change, increased costs for producers, lack of labor and volatility in coffee prices are having a significant impact on the coffee industry, and could be underlying reasons behind the declining trends. In the yields observed in some producing countries, as well as in some regions traditionally dedicated to coffee production in Colombia. These trends pose significant challenges for the sector and require careful evaluation of the strategies and policies that are implemented in the future to ensure the sustainability and competitiveness of the coffee industry locally and internationally.